Psychological features of the coping behavior of military officers and the civilian population in combat conditions - Mushkevych, Valentun; Pasichnuk, Lesya (Psychological Prospects Journal, 2022)
The purpose of the article involves the study of the main psychological features of coping strategies of military personnel and civilians in the conditions of hostilities. Factorization by the method of principal components with varimax rotation of the matrix of psychological indicators of coping strategies of military personnel and the civilian population in the conditions of hostilities was carried out.Methods. To diagnose the coping strategies of military personnel and the civilian population in the conditions of hostilities, the following methods and techniques were used, such as observation, conversation, questionnaires, testing: the questionnaire «Coping behavior in stressful situations» C Norman. These methods are widely used for the study of maladaptive forms of coping strategies in persons who are in stressful situations, for the correction of their coping behavior; for group or individual psychotherapy; for drawing up psychohygienic and psychoprophylactic programs taking into account the formation of adaptive forms of coping behavior.Results. According to the results of the empirical study, it was established that problem-oriented coping, cognitive relatively adaptive coping strategies and behavioral relatively adaptive coping strategies dominate both in the military and in the civilian population. The lowest indicators correspond to the manifestation of emotional coping strategies, at the same time, when comparing emotional adaptive, relatively adaptive and maladaptive strategies, both military personnel and civilians demonstrate a high level of adaptive emotional coping, which implies the presence of a positive outlook on life and confidence, that you can find a way out of any situation. It has been proven that the subjects of both samples demonstrate coping focused on the stressful situation itself and its representation, namely: striving to better understand the situation, searching for information, leaving the traumatic situation.Conclusions. The vast majority of respondents in both samples have a sufficient awareness of their own resilience, which increases adaptability, the ability to adapt to difficult situations, unpredictable life changes in the conditions of hostilities, as well as a high level of open, free planning, which makes it possible to use new ones every time, in accordance with the actual situations, ways of setting life tasks.
Keywords: military personnel; civilian population; coping strategies; behavioral strategies; combat operations; resilience